Sensory Impact of 2-Methoxy-3-Isobutylpyrazine and 4-Mercapto-4- Methylpentan-2-0ne Added to a Neutral Sauvignon blanc Wine - Marais, J.; Swart, E. (South African Journal of Enology and Viticulture, 2017)
2-Methoxy-3-isobutylpyrazine (ibMP) and 4-mercapto-4-methylpentan-2-one (MMP) are considered amongst the most important Sauvignon blanc impact aroma components. These two components were added, separately and in combination at increasing concentrations, to different media, i.e. deionised water, a neutral non-Sauvignon blanc white wine and a neutral Sauvignon blanc wine. The media were then sensorially evaluated. The nuances perceived, varied from dusty, grassy to green pepper for ibMP and from guava, sulphur-like to cat urine or "conifer" for MMP. It was confirmed that ibMP and MMP are important impact components and that their contribution, either positive or negative, varied according to medium type and composition, as well as to the concentration levels of the components. This may be ascribed to the combined synergistic action of these two components. Other typical Sauvignon blanc aroma nuances, such as asparagus, gooseberry, passion fruit and fig were not detected and the relationship between these aromas and other Sauvignon blanc aroma impact components needs to be further investigated.